Optimalisasi Sosial Media Marketing untuk Meningkatkan Konversi Penjualan pada Usaha Catering Rumahan - Salwa Az Zhahra Putri; Acep Samsudin (Universitas Maritim AMNI Semarang, 2023)
The development of the internet has affected all aspects of human activity including marketing. Social media marketing is a marketing strategy by utilizing social media platforms. For this reason, every business needs to pay attention to social media as a very important promotional medium. This research journal aims to prove the importance of optimizing social media marketing for increasing sales conversions carried out at the 'Dapur Mamiku' catering business. The process of increasing sales is carried out by assisting business actors and optimizing social media. The final stage of this research will be an analysis and evaluation of the research that has been done. The results of this study are expected to give a greater impression/reach to potential customers and increase sales conversions for 'Dapur Mamiku' catering products.